Ensuring Food Security in the Context of the Development of Integration Processes - SAGINOVA, Saniya; ABELDINA, Rauza; BIRYUKOV, Valeriy; SAPAROVA, Gulnar; TEMIRBULATOV, Alken; YSSUPOVA, Saltanat (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.v9.5(29).25, 2019)
Food security is one of the main objectives of the agrarian and economic policy of the state. In its general form, it forms the vector of movement of any national food system to an ideal state. Analysis of indicators of the state of the food market and the provision of the population with food, the selection of the most optimal of them for making effective management decisions is an important task in developing a strategy for ensuring the country's food security. Therefore, the purpose of this article is to assess food security in the Republic of Kazakhstan. The article analyses the statistical data of the Republic of Kazakhstan on ensuring food security in the country.